Renal phenotyping in a hypomorphic murine model of propionic aciduria reveals common pathomechanisms in organic acidurias - Anke Schumann; Ainhoa Martinez-Pizarro; Eva Richard; Christoph Schell; Anna Laura Kössinger; Karina A. Zeyer; Stefan Tholen; Oliver Schilling; Michael Barry; Björn Neubauer; Michael Köttgen; Luciana Hannibal; et al. (Scientific Reports)
Abstract Mutations in the mitochondrial enzyme propionyl-CoA carboxylase (PCC) cause propionic aciduria (PA). Chronic kidney disease (CKD) is a known long-term complication. However, good metabolic control and standard therapy fail to prevent CKD. The pathophysiological mechanisms of CKD are unclear. We investigated the renal phenotype of a hypomorphic murine PA model (Pcca -/- (A138T)) to identify CKD-driving mechanisms. Pcca -/- (A138T) mice show elevated retention parameters and express markers of kidney damage progressing with time. Morphological assessment of the Pcca -/- (A138T) mouse kidneys indicated partial flattening of tubular epithelial cells and focal tubular-cystic dilation. We observed altered renal mitochondrial ultrastructure and mechanisms acting against oxidative stress were active. LC–MS/MS analysis confirmed disease-specific metabolic signatures and revealed disturbances in mitochondrial energy generation via the TCA cycle. Our investigations revealed altered mitochondrial networks shifted towards fission and a marked reduction of mitophagy. We observed a steep reduction of PGC-1-α, the key mediator modulating mitochondrial functions and a counter actor of mitochondrial fission. Our results suggest that impairment of mitochondrial homeostasis and quality control are involved in CKD development in PA. Therapeutic targeting of the identified pathways might help to ameliorate CKD in addition to the current treatment strategies.